The retrieval of fingerprint friction ridge detail from elephant ivory using reduced-scale magnetic and non-magnetic powdering materials. Issue 1 (January 2016) - Weston-Ford, Kelly A.; Moseley, Mark L.; Hall, Lisa J.; Marsh, Nicholas P.; Morgan, Ruth M.; Barron, Leon P.
Abstract: An evaluation of reduced-size particle powdering methods for the recovery of usable fingermark ridge detail from elephant ivory is presented herein for the first time as a practical and cost-effective tool in forensic analysis. Of two reduced-size powder material types tested, powders with particle sizes ≤ 40 μm offered better chances of recovering ridge detail from unpolished ivory in comparison to a conventional powder material. The quality of developed ridge detail of these powders was also assessed for comparison and automated search suitability. Powder materials and the enhanced ridge detail on ivory were analysed by scanning electron microscopy and energy dispersive X-ray spectroscopy and interactions between their constituents and the ivory discussed. The effect of ageing on the quality of ridge detail recovered showed that the best quality was obtained within 1 week. However, some ridge detail could still be developed up to 28 days after deposition. Cyanoacrylate and fluorescently-labelled cyanoacrylate fuming of ridge detail on ivory was explored and was less effective than reduced-scale powdering in general. This research contributes to the understanding and potential application of smaller scale powdering materials for the development of ridge detail on hard, semi-porous biological material typically seized in wildlife-related crimes. Graphical abstract: Highlights: Reduced scale magnetic powders outperformed conventional powders for mark enhancement on seized elephant ivory. The effect of fingermark age on ivory significantly affected enhancement success. Usable marks were still recovered after 28 days, but the best results were obtained within 7 days. No improvement in mark quality using CNA enhancement or when used in sequence with powders